2010
DOI: 10.1097/spv.0b013e3181ec1edd
|View full text |Cite
|
Sign up to set email alerts
|

Allogenic Myoblast Transplantation in the Rat Anal Sphincter

Abstract: : This demonstrates that myoblasts can be successfully extracted, cultivated in vitro, transplanted and will integrate into the host tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…(See prior publication from this laboratory for detailed methodology of transduction and engraftment). 4 Final concentration in all groups (with and without GFP and/or HGF) consisted of 5 Â 10 6 myoblasts and associated MSCs.…”
Section: Cellsmentioning
confidence: 99%
“…(See prior publication from this laboratory for detailed methodology of transduction and engraftment). 4 Final concentration in all groups (with and without GFP and/or HGF) consisted of 5 Â 10 6 myoblasts and associated MSCs.…”
Section: Cellsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Previously, our group published data that transplanted msCs can survive and fuse with host muscle. myogenic stem cells are derived from satellite cells that lie between the basal lamina and sarcolemma of adult muscle fibers.…”
mentioning
confidence: 99%
“…Previous studies indicate that stem cells are incorporated into injured anal sphincter. 28,29 Studies in other models of tissue injury indicate that stem cells improve organ function through secretion of antiinflammatory proteins. 30 Our study did not address this issue but demonstrated functional improvement of the sphincter with stem cell injection.…”
Section: Discussionmentioning
confidence: 99%